Maternal and perinatal outcome in antepartum hemorrhage - Reddy, Aamani; D., Suchetha; K., Swathi; G., Mahalakshmi (International Journal of Research in Medical Sciences, 2024)
Background: Antepartum hemorrhage (APH) is defined as bleeding from or into the genital tract, occurring from 24+0 weeks of gestation and prior to delivery. Placenta previa (PP) and abruptio placenta (AP) constitute the two main causes of APH. The condition is associated with severe maternal and perinatal morbidity and mortality. The incidence has been on the rise due to increased incidence of operations in the current era. The objectives of the study are to determine the proportion, to assess the feto maternal outcome of APH and the risk factors associated with the maternal and fetal morbidity and mortality. Methods: A prospective observational study conducted in the department of obstetrics and gynecology at Gandhi hospital from January 2021 to June 2022. All the women with complaints of bleeding per vaginum were included in the study after obtaining consent. The feto maternal outcome was monitored and noted down and statistical analysis was done. Results: The 100 antenatal women with bleeding per vaginum were included in the study. The results showed that majority of APH cases were among multigravida in the age group of 21-25 years. and in the gestational age of 36-38 weeks. Hypertensive disorder of pregnancy was the most common risk factor identified for abruption. LSCS was the most common mode of termination of pregnancy and postpartum hemorrhage (PPH) is the most common complication encountered. There were 3 maternal deaths. Conclusions: APH is still a leading cause of maternal morbidity and mortality in our country. Awareness of pregnant women about the importance of regular antenatal checkups and easy accessibility to antenatal services go a long way in bringing down the maternal and perinatal morbidity and mortality related with APH.